2017
DOI: 10.1038/ja.2017.118
|View full text |Cite
|
Sign up to set email alerts
|

Ascosteroside D, a new mitochondrial respiration inhibitor discovered by pesticidal screening using insect ADP/ATP carrier protein-expressing Saccharomyces cerevisiae

Abstract: A new lanostane-type triterpenoid, ascosteroside D, was isolated from a fungus, Aspergillus sp. FKI-6682. It inhibited insect ADP/ATP carrier protein (AAC)-expressing Saccharomyces cerevisiae in glycerol-containing medium, but did not inhibit Δaac S. cerevisiae in glucose-containing medium. It is hypothesized that ascosteroside D inhibits ATP production in mitochondria.The Journal of Antibiotics advance online publication, 11 October 2017; doi:10.1038/ja.2017.118.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[19,35] Recently, it has been hypothesized that a lanostane-type triterpenoid, ascosteroside D, isolated from a fungus (Aspergillus), inhibits insect ATP production in mitochondria. [36] The study of the structure -activity relationships (SAR) of the test compounds showed that overall, the substituents at C-3 and C-7/C-8 modulated the insecticidal activity of these derivatives ( Table 4). Acetylation at C-3/epoxidation at C-8 gave the maximum insecticidal effect (1), followed by carbonyl groups at C-3/C-7 with additional hydroxy groups (C-8, C-25) (6, 8) or C-3 carbonyl and C-7 epoxide with C-8 unsaturation (7, 9).…”
Section: Resultsmentioning
confidence: 99%
“…[19,35] Recently, it has been hypothesized that a lanostane-type triterpenoid, ascosteroside D, isolated from a fungus (Aspergillus), inhibits insect ATP production in mitochondria. [36] The study of the structure -activity relationships (SAR) of the test compounds showed that overall, the substituents at C-3 and C-7/C-8 modulated the insecticidal activity of these derivatives ( Table 4). Acetylation at C-3/epoxidation at C-8 gave the maximum insecticidal effect (1), followed by carbonyl groups at C-3/C-7 with additional hydroxy groups (C-8, C-25) (6, 8) or C-3 carbonyl and C-7 epoxide with C-8 unsaturation (7, 9).…”
Section: Resultsmentioning
confidence: 99%